(untitled) (Swiss Medical Weekly, 2014)
BACKGROUND AND STUDY PURPOSE: To assess the incidence of cardiac and metabolic adverse events in very low birth weight (VLBW) infants receiving systematic steroids. PATIENTS AND METHODS: Prospective single centre audit in VLBW infants (<1,500 g) at the neonatal intensive care unit at the University Children’s Hospital of Saarland, Germany. RESULTS: A total of 72 VLBW infants (38 female) were included in this report (mean birth weight: 967 ± 338 g; range: 320–1490 g). Birth weight, gestational age and Apgar scores were significantly lower in the steroid group (p <0.01). Mortality rate was 8/72 (7/34 in the steroid treated vs nontreated 1/38; odds ratio [OR]: 9.6; 95% confidence interval [CI]: 1.1–82.6 p = 0.02). In 34/72 infants, steroids were given (22 hydrocortisone alone; 12 combination of hydrocortisone and dexamethasone). The most common indication for use of steroids was respiratory distress syndrome (RDS) and respiratory insufficiency (30/34). Adverse events that occurred more often in the steroid group included hypertrophic cardiomyopathy (14/34 vs 0/38; p <0.001); thrombus formation (8/34 vs 1/38; OR: 11.4; 95% CI: 1.3-96.6; p <0.05), hyperglycaemia (27/34 vs 3/38; OR: 45.0; 95% CI: 10.6–190.4; p <0.01), hypernatraemia (15/34 vs 7/38; OR: 3.5; 95% CI: 1.2–10.1; p <0.05), and sepsis/infections (8/34 vs 1/38; OR: 11.4; 95% CI: 1.3–96.6; p <0.05). No significant differences were seen between hydrocortisone alone and the combination of hydrocortisone with dexamethasone. Birth weight and severity of RDS were predictors of steroid use (p <0.01). CONCLUSIONS: The use of steroids was significantly associated with severe short-term adverse events – most importantly hypertrophic cardiomyopathy and thrombus formation. These complications must be taken into consideration when administering steroids to VLBW infants.